SARS-CoV-2 infection in the Indigenous Pataxó community of Southern Bahia, Brazil: second wave of transmission and vaccine effects - Luciano Rodrigues Reis; Maria Helena Feres Saad (Cadernos de Saúde Pública)
Indigenous people are at risk of several infectious diseases, including viruses that affect the respiratory system. In a previous study, we demonstrated how the Pataxó ethnic group, in the southernmost region of Bahia State, Brazil, was disproportionately affected during the first wave of COVID-19. Here, we provide an overview of how this community was affected by the second wave of the disease, evaluating the impact of vaccination on SARS-CoV-2 transmission. Prospective study data was grouped by Epidemiological Weeks 3/2021-43/2022, during which vaccine effects were analyzed and new variants of concern (VOC) emerged. The second wave produced a decreasing trimodal moving average curve, with an incidence rate of 4,407.2/100,000 inhabitants. Mobility and precarious work situations linked to tourism and craft trade increased infection rates in some villages. Risk factors for infection and severity (female sex, older age, and comorbidities) were determinants, but mortality was lower. Individuals with two doses of vaccine (Vac) developed more symptoms than the unvaccinated, but were less likely to have dyspnea. The mean time for COVID-19 symptoms to develop was longer in those with Vac (x̅ = 27 weeks) compared to those who received only one dose (x̅ = 12 weeks, p ≤ 0.001). Vac individuals who received booster shots, VacB1 and VacB2, had infection rates of 7.4% and 0%, respectively. The detrimental impact of COVID-19 once again highlights the persistence of health and socioeconomic inequities in this ethnic group. Moreover, the vaccines failed to prevent transmission, possibly due to mutated VOCs, but they may have protected this group against severe symptoms and extended the transmission period.